Liberating Augustine Rethinking Augustine’s emphasis on interiority1 - Bedford, Nancy Elizabeth 1962- (2017)
Has Augustine’s emphasis on interiority, along with his ideas about how to imagine the Trinity, been a negative influence on “Western” (in the sense of Protestant and Catholic) theology? Jürgen Moltmann has been very critical of Augustine’s influence in this regard, as have other theologians, including many feminists. The essay problematizes that claim from the perspective of subaltern subjectivities and the construction of personhood in situations of vulnerability.
Keywords: Agency; Augustine; Interiority; subaltern subjects; Subjectivity; Trinity